Bentuk Penolakan Tokoh terhadap Adat Suku Minangkabau dalam Novel Memang Jodoh Karya Marah Rusli (Kajian Sosiologi Sastra Ian Watt) - Hajiku, Nurtia; Hinta, Ellyana; Umam Kau, Munkizul (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
This study aims to describe the portrayal of customs, matchmaking, marriage, and kinship systems in the Minangkabau community as depicted in the novel Memang Jodoh by Marah Rusli. The approach employed is Ian Watt's sociology of literature, which emphasises the reflection of society in novels, the influence of the author's social context, and the role of literature within society. The research method is qualitative descriptive, with data collection techniques involving reading and noting excerpts related to matchmaking in the novel. The findings reveal several points. First, the story portrays Minangkabau customs, focusing on the matrilineal system, marriage traditions, and religious-based customs. Second, the rejection of matchmaking reflects the social conditions of the community and Marah Rusli's view of changing perceptions of customary rules. Third, the rejection of marriage customs shows that the Minangkabau community still upholds traditional values, although Marah Rusli argues that marriage rules should not limit individual freedom. Fourth, the rejection of the kinship system reflects the matrilineal reality and Marah Rusli's effort to reform it to remain relevant to society. Overall, Ian Watt's sociology of literature demonstrates that literature reflects customary realities and plays a role in social change